Mathematical Foundations of Computer Science 2015 : 40th International Symposium, MFCS 2015, Milan, Italy, August 24-28, 2015, Proceedings, Part II - Italiano, Giuseppe F.; Pighizzini, Giovanni; Sannella, Donald T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This two volume set LNCS 9234 and 9235 constitutes the refereed conference proceedings of the 40th International Symposium on Mathematical Foundations of Computer Science, MFCS 2015, held in Milan, Italy, in August 2015. The 82 revised full papers presented together with 5 invited talks were carefully selected from 201 submissions. The papers feature high-quality research in all branches of theoretical computer science. They have been organized in the following topical main sections: logic, semantics, automata, and theory of programming (volume 1) and algorithms, complexity, and games (volume 2).
Keywords: Computer software; Computational complexity; Electronic data processing; Data structures (Computer scienc; Computer science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Data Structures; Mathematical Logic and Formal Languages; Math Applications in Computer Science